Konsep Falah dalam Pembangunan Ekonomi Makro Modern - Athiul Aulia; Imahda Khoiri Furqon; Shulhah Nurullaily (FEBI UIN Sunan Kalijaga, 2025)
This study examines the concept of falah in modern economic development and argues that it offers a comprehensive framework for evaluating economic progress beyond mere material growth. The purpose of this study is to explain how falah integrates spiritual, moral, social, and economic dimensions into an integrated development perspective. This study uses a literature review method by analyzing relevant Islamic texts, scientific artifacts, and economic development. The findings show that falah redefines development success as the achievement of balanced prosperity in this world and the hereafter, not just an increase in income or output. Emphasizing justice, fair distribution, social responsibility, human development, and environmental sustainability as important indicators of a successful economy, the study also found that Islamic economic instruments such as zakat, waqf, alms, and ethical policy design can operationalize falah into development to encourage inclusive economic growth. Humane, and sustainable. This framework is particularly relevant in addressing inequalities, poverty, and ecological degradation in the modern economy. The originality of this study lies in its focused synthesis of falah as a normative and practical paradigm for modern economic development, which offers an alternative to conventional growth-centric models.